2013
DOI: 10.3109/15412555.2013.858316
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Periodontal Disease and Chronic Obstructive Pulmonary Disease: A Case Control Study

Abstract: Our results demonstrated that COPD may be associated with periodontal disease as manifested by lower number of teeth and higher levels of inflammatory mediators especially CRP in GCF. This finding may be a reflection of systemic effects of COPD on periodontal tissues. Poor oral health behavior of COPD patients have to be considered in larger size group studies in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 37 publications
1
27
1
4
Order By: Relevance
“…Similar to Öztekin et al, 29 the present study shows that number of teeth was significantly lower in patients with COPD. Furthermore, poor periodontal health was associated with dental loss, may have contributed to systemic inflammation, and was associated with COPD.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to Öztekin et al, 29 the present study shows that number of teeth was significantly lower in patients with COPD. Furthermore, poor periodontal health was associated with dental loss, may have contributed to systemic inflammation, and was associated with COPD.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, poor periodontal health was associated with dental loss, may have contributed to systemic inflammation, and was associated with COPD. Öztekin et al 29 also showed that serum and gingival crevicular fluid high‐sensitive C‐reactive protein levels were significantly higher in patients with COPD than in controls. Periodontitis may be linked to COPD through microbial species, by supporting colonization of respiratory pathogens in dental plaque 28 or by airway inflammation and exacerbation by periodontal organisms.…”
Section: Discussionmentioning
confidence: 96%
“…9 In the year 2014, Öztekin et al in their study noted that there is association between the periodontal diseases and COPD. 10…”
Section: Various Systemic Diseases With Their Oral Manifestation Pulmmentioning
confidence: 99%
“…COPD inflammatory status may be modified by dental plaque and/or hematogenous dissemination of inflammatory mediators and plaque microorganism from periodontal pockets [47]. Oztekin, et al also showed that serum and gingival crevicular fluid high-sensitive C-reactive protein levels were significantly higher in patients with COPD than in controls [55]. Neutrophils also play an important role in both COPD and periodontitis, as their proteases and reactive oxygen species can promote inflammation and destroy CT [56].…”
Section: Bmimentioning
confidence: 99%